Experiences Of Frontline Nurses Managing Patients With Coronavirus Disease At Ga East Municipal Hospital, Accra - Atuwo – Ampoh, E.E. (University Of Ghana, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has affected many healthcare systems globally. Its impact was considered a serious risk to healthcare providers and had far reaching consequences on their lives. In Ghana, treatment centers were designated to help patients isolate for treatment under the care of healthcare workers. Frontline nurses managing patients with COVID-19 experienced physical and psychological challenges whilst on their duty and were perceived as carriers of coronavirus. This study aimed to explore the nurses’ experiences managing patients with COVID-19 at the Ga East Municipal Hospital, Accra. The ABC-X model of family stress and coping developed by Hill in 1949 underpinned this study. The study employed an exploratory descriptive qualitative research design to explore and describe the experiences of fourteen (14) purposively sampled nurses using a semistructured interview guide. The interviews were audiotaped with participants’ permission, transcribed verbatim, and analyzed using thematic content analysis. This study’s findings identified four themes: COVID-19 care challenges, multi-dimensional support, care-related stressors, and perceived care outcomes. The frontline nurses experienced some physical and psychological stressors whilst managing patients with COVID-19 at Ga East Municipal Hospital. They were also perceived as carriers of coronavirus who might infect their friends and family. The nurses utilized diverse strategies and support from various individuals and groups as the pandemic unfolded. The frontline nurses-built resilience amidst the challenges encountered. The stressful experiences of the frontline nurses and other healthcare personnel in the facility should be considered and addressed, with sustainable interventions outlined to reduce the stress on healthcare workers.
MPhil. Nursing
Keywords: Accra; Ga East Municipal Hospital; Coronavirus Disease; Frontline Nurses